Review on Hydrogenation of Biomass Derived 5-Hydroxymethylfurfural to 2,5-Dimethylfuran - Lu, Hue Phuoc (Journal of Technical Education Science, 2025)
Biofuels play a crucial role as potential substitutes for fossil fuels in the transition towards sustainable energy systems. Among these bioenergy carriers, 2,5-dimethylfuran (2,5-DMF) has emerged as a promising alternative fuel due to its favorable physicochemical properties. Biomass resources such as cellulose and hemicellulose the two principal structural components of lignocellulosic biomass can be converted via hydrolysis and pyrolysis into a range of biomass-derived fuels. This conversion pathway is of particular significance for the sustainable utilization of renewable resources in support of green and circular economies. Recent advances in the catalytic transformation of 5-hydroxymethylfurfural (5-HMF) from biomass into 2,5-DMF via selective dehydration are reviewed, with a focus on reaction mechanisms, single-metal catalysts (Ru-, Pt-, Cu-, and Ni-based), bimetallic catalysts, and various solvent systems, including tetrahydrofuran, alcohols, acids, water, and biphasic systems. Notably, 2,5-DMF derived from biomass exhibits a high energy density, elevated octane number, immiscibility with water yet high miscibility with gasoline, along with advantages such as high productivity, low initial capital cost, and the capacity to valorize agricultural by-products.